Optimization of Intra-Row Spacing for Yield Enhancement in System of Mustard Intensification (SMI) Techniques - Pandit, Tapas Kumar; Roy, Shyamashree; Das, Bimal (International Journal of Bio-resource and Stress Management, 2022)
The experimental work was carried out during the rabi seasons (November to February) of the year 2018 and 2019 at Instructional field of RRS (OAZ), Uttar Banga Krishi Viswavidyalaya, Majhian, Dakshin Dinajpur, West Bengal, India to study the growth and yield performance of different varieties from toria, rapeseed and Indian mustard with three different spacing combinations under System of Mustard Intensification (SMI) technology. The seedlings were raised in micro-pots (2×2.5 cm2 size) and transplanted in the main plot. The experiment was laid out in a completely randomized block design replicated thrice. The treatments consisted of three levels of plant spacing (25×25 cm2, 45×45 cm2, 60×60 cm2) and included 3 varieties one each from toria, rapeseed and Indian mustard group. Among different treatment combinations, variety Bhagirathi (from Indian mustard group), in combination with spacing of 60×60 cm2 (S3V3) was recorded with highest yield (1348.08 kg ha-1) followed by its rest of the combinations with 25×25 cm2 (1331.42 kg ha-1) and 45cm×45 cm (1320.67 kg ha-1), i.e. S1V3 and S2V3, respectively. Plant height (cm) was also recorded highest with S3V3 treatment followed by S2V3 and S1V3. Total chlorophyll (mg 100 g-1) content was recorded highest with the same Bhagirathi variety S1V3 treatment (18.99) followed by S2V3 (17.45) and S3V3 (17.61). Amongst the yield attributing characters, number of secondary branches, number of siliqua plant-1 and total chlorophyll content were recorded highest with the Bhagirathi variety from the Indian mustard group with the spacing of 60×60 cm2 (S3V3).